The Growth of Green and Sustainable Finance in Islamic Banking: A Bibliometric Approach - Bekti Bekti Utomo; Eko Sudarmanto; Muhammadong Muhammadong (Sciences du Nord Economics and Business, 2024)
This study employs a bibliometric analysis to explore the intersection of Islamic banking and sustainable finance, focusing on the integration of environmental, social, and governance (ESG) criteria into Islamic financial practices. Utilizing data from Google Scholar, this research maps the landscape of green and sustainable finance within Islamic banking from 2001 to 2024. The analysis identifies core themes such as green sukuk, ESG investing, and climate finance, and examines their connectivity and evolution over time. The results reveal a growing emphasis on aligning Islamic finance with global sustainability goals, highlighted by the increasing prominence of green financial instruments and sustainability-focused financial services. However, challenges such as the need for standardized regulatory frameworks and greater incorporation of technological innovations in financial practices persist. The study suggests that addressing these challenges through clearer guidelines and enhanced financial technology could propel Islamic banking into a more significant role in global sustainability efforts.